2011
DOI: 10.1097/cad.0b013e3283400a20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the mTOR inhibitor, everolimus, in combination with cytotoxic antitumor agents using human tumor models in vitro and in vivo

Abstract: The aim was to determine the potential of the allosteric mammalian target of rapamycin inhibitor, everolimus, to act in combination with cytotoxic anticancer compounds in vitro and in vivo. A concomitant combination in vitro showed no evidence of antagonism, but enhanced the antiproliferative effects (additive to synergistic) with cisplatin, doxorubicin, 5-fluorouracil, gemcitabine, paclitaxel, and patupilone. Everolimus (1-5 mg/kg/d orally) was evaluated for antitumor activity in vivo alone or in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 27 publications
1
47
1
Order By: Relevance
“…Despite only marginal ORR, relevant disease control rates (27-51%) were likewise observed. Nevertheless, in spite of encouraging preclinical data showing synergistic effects by combining everolimus with paclitaxel, the results of our trial were below our expectations [8]. …”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Despite only marginal ORR, relevant disease control rates (27-51%) were likewise observed. Nevertheless, in spite of encouraging preclinical data showing synergistic effects by combining everolimus with paclitaxel, the results of our trial were below our expectations [8]. …”
Section: Discussioncontrasting
confidence: 52%
“…In preclinical models, the efficacy of paclitaxel could be increased by the addition of everolimus [8]. Everolimus is an inhibitor of the PI3K/pAkt pathway targeting the serine/threonine kinase mTOR [9].…”
Section: Introductionmentioning
confidence: 99%
“…Everolimus indeed induces massive autophagy in vivo, with reduced tumoral mass, for example in leukemia [76], in advanced pancreatic tumors [77] and in many other tumors [78]. Concomitant combinations of etoposide, cisplatin or doxorubicin with everolimus produced cooperative antitumor effects, in some cases producing regressions without clinically significant increases in toxicity [79]. One mechanism responsible for this synergy is the activation of p53 by the DNA damaging agent.…”
Section: To Provoke Cell Deathmentioning
confidence: 99%
“…While rapalogs display favorable characteristics in cell culture, such as induction of apoptosis and inhibition of proliferation, migration and invasion of CRC cells (Fujishita et al 2008;Gulhati et al 2011;O'Reilly et al 2011), their effectiveness as a stand-alone treatment in CRC patients has proved limited (Altomare and Hurwitz 2013;Ng et al 2013). However, preclinical studies have demonstrated cooperative antitumor effects using rapalogs in combination with cisplatin, doxorubicin or paclitaxel (O'Reilly et al 2011). There are currently several clinical trials assessing the efficacy of rapalogs in combinations with other chemotherapeutic drugs, especially in advanced CRCs or as a second-line treatment (see clinicaltrials.gov).…”
Section: Translation and Colorectal Cancer Therapymentioning
confidence: 95%
“…These compounds have received much attention in CRC, as various components of the mTOR pathway, including mTORC1, mTORC2, AKT1, AKT2 and others are elevated and/or activated in these cancers (Fujishita et al 2008;Gulhati et al 2011;Johnson et al 2010). While rapalogs display favorable characteristics in cell culture, such as induction of apoptosis and inhibition of proliferation, migration and invasion of CRC cells (Fujishita et al 2008;Gulhati et al 2011;O'Reilly et al 2011), their effectiveness as a stand-alone treatment in CRC patients has proved limited (Altomare and Hurwitz 2013;Ng et al 2013). However, preclinical studies have demonstrated cooperative antitumor effects using rapalogs in combination with cisplatin, doxorubicin or paclitaxel (O'Reilly et al 2011).…”
Section: Translation and Colorectal Cancer Therapymentioning
confidence: 99%